VACCINATION AGAINST PNEUMOCOCCAL INFECTION DURING THE PREPARATION FOR A PROBABLE FLU PANDEMIC - M.V. Fedoseenko; M.G. Galitskaya; L.S. Namazova (Union of pediatricians of Russia, 2008)
The vaccination against pneumococcal infection during the preparation for a probable flu pandemic has recently been given a significant role. The authors found out that the attachment of the secondary bacterial infection is an important cause for the morbidity and mortality during the flu pandemic. The pneumococcus has been acknowledged to be the main causative agent, causing up to 50% of the secondary bacterial pneumonias during the flu pandemic. The interepidemic period and pandemic prevention period are the ideal time to carry out preventive actions, as the full scale pneumococcal vaccination is not feasible when the flu pandemic breaks out.Key words: flu pandemic, pneumococcal infection, vaccination, children.